Networking dalam Medukung Perempuan Berwirausaha: Sistematis Literatur Review - Musrifah, Musrifah; Andriani, Nurita; Hasanah, Uswatun (LPPM Institut Pendidikan Nusantara Global, 2025)
Women entrepreneurs play a crucial role in strengthening micro, small, and medium enterprises (MSMEs) and contributing to economic growth, particularly in developing countries such as Indonesia. Despite their increasing participation, women entrepreneurs continue to face various challenges, including gender discrimination, limited access to resources, and insufficient structural support. In this context, networking emerges as a strategic factor that supports women’s entrepreneurial success by facilitating access to information, resources, collaboration, and emotional support. This study aims to systematically examine the role of networking in supporting women entrepreneurs through a Systematic Literature Review (SLR). Academic articles published between 2015 and 2025 were collected from reputable databases, including Google Scholar and PubMed, using keywords related to women entrepreneurship and networking. A total of 13 relevant journal articles met the inclusion criteria and were analyzed using a thematic approach to identify key patterns and contributions. The findings indicate that networking functions not only as economic capital but also as social and psychological capital that enhances women entrepreneurs’ confidence, resilience, and competitiveness. Strong social networks enable women entrepreneurs to access business opportunities, expand markets, share knowledge, and overcome gender-based barriers. Furthermore, community-based and organizational networks play an important role in fostering collaboration, mentorship, and policy advocacy. This study highlights the importance of strengthening inclusive and sustainable networking programs to support women entrepreneurs. The findings provide valuable insights for policymakers, practitioners, and women entrepreneurs in designing effective strategies to enhance entrepreneurial success and promote gender-inclusive economic development.